REMOTE HEALTH MONITORING: FALL DETECTION - Mohamad ABDULHAMID (Applied Computer Science, 2020)
Falling is a serious health issue among the elderly population; it can result in critical injuries like hip fractures. Immobilization caused by injury or uncon-sciousness means that the victim cannot summon help themselves. With elderly who live alone, not being found for hours after a fall is quite common and drastically increases the significance of fall-induced injuries. With an aging Baby Boomer population, the incidence of falls will only rise in the next few decades. The objective of this paper is to design and create a fall detection system. The system consists of a monitoring device that links wirelessly with a laptop. The device is able to accurately distinguish between fall and non-fall.